Facial Anthropometric Norms among Kosovo - Albanian Adults - Gloria Staka; Flurije Asllani-Hoxha; Venera Bimbashi (University of Zagreb. School of Dental Medicine, 2017)
The development of an anthropometric craniofacial database is a necessary multidisciplinary proposal. Aim: The aim of this study was to establish facial anthropometric norms and to investigate into sexual dimorphism in facial variables among Kosovo Albanian adults. Materials and Methods: The sample included 204 students of Dental School, Faculty of Medicine, University of Pristina. Using direct anthropometry, a series of 8 standard facial measurements was taken on each subject with digital caliper with an accuracy of 0.01 mm (Boss, Hamburg-Germany). The normative data and percentile rankings were calculated. Gender differences in facial variables were analyzed using t- test for independent samples (p<0.05). The index of sexual dimorphism (ISD) and percentage of sexual dimorphism were calculated for each facial measurement. Results: Normative data for all facial anthropometric measurements in males were higher than in females. Male average norms compared with the female average norms differed significantly from each other (p>0.05).The highest index of sexual dimorphism (ISD) was found for the lower facial height 1.120, for which the highest percentage of sexual dimorphism, 12.01%., was also found. The lowest ISD was found for intercanthal width, 1.022, accompanied with the lowest percentage of sexual dimorphism, 2.23%. Conclusion: The obtained results have established the facial anthropometric norms among Kosovo Albanian adults. Sexual dimorphism has been confirmed for each facial measurement.